2009
DOI: 10.1016/j.ydbio.2009.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Abd-B suppresses lepidopteran proleg development in posterior abdomen

Abstract: Pterygotes lack abdominal appendages except for pleuropods and prolegs. The larvae of some holometabolous insects develop prolegs, which are used for locomotion. We analyzed the role of the homeotic genes abd-A and Abd-B in lepidopteran proleg development using mutant analysis and embryonic RNAi in the silkworm Bombyx mori. The E(Mu) mutant developed extra prolegs in its posterior abdomen and showed the misexpression of both genes, suggesting their involvement in proleg formation. The depletion of Abd-B by emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 28 publications
5
46
0
2
Order By: Relevance
“…This suggests that Abd-B may function as an activator of PO formation, initiating PO-specific gene expression in A6/7 while overseeing the ventral repression of pigmentation pathways through A5. This demonstrates a surprisingly anterior role for Abd-B compared to other insects studied, such as silkworm proleg suppression in A7-A10 [31], or scent gland suppression (A7) and pigment induction in A10-A11 in Oncopeltus [32]. In the most closely related insect studied to date, embryos of the flour beetle Tribolium castaneum express Abd-B transcripts no further than the posterior compartment of A8 [33].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that Abd-B may function as an activator of PO formation, initiating PO-specific gene expression in A6/7 while overseeing the ventral repression of pigmentation pathways through A5. This demonstrates a surprisingly anterior role for Abd-B compared to other insects studied, such as silkworm proleg suppression in A7-A10 [31], or scent gland suppression (A7) and pigment induction in A10-A11 in Oncopeltus [32]. In the most closely related insect studied to date, embryos of the flour beetle Tribolium castaneum express Abd-B transcripts no further than the posterior compartment of A8 [33].…”
Section: Discussionmentioning
confidence: 99%
“…In hexapods, Abd -B is typically expressed from the posterior of A8 to the posterior terminus of the embryo (Hughes and Kaufman 2002 ). Functional data show that Abd -B suppresses embryonic appendage development in Bombyx (Tomita and Kikuchi 2009 ) and Drosophila (Vachon et al 1992 ). The loss of embryonic and juvenile appendages on A8-A10 occurred early in insect evolution, whereas the A11 appendages evolved into cerci that are retained in many extant lineages (but absent in Paraneoptera and many or all Holometabola; Fig.…”
Section: Loss Of Abdominal Appendagesmentioning
confidence: 99%
“…The Hox genes are downregulated in circular patches in the prolegforming segments, Dll expression is initiated throughout these patches, and the proleg primordia begin to grow (Fig. 3.21G, H ;Warren et al 1994 ;Suzuki and Palopoli 2001 ;Tomita and Kikuchi 2009 ). After proleg outgrowth has been initiated, abd -A is subsequently required for their maintenance in A3-A6 (Tomita and Kikuchi 2009 ;Chen et al 2013 ).…”
Section: Re-evolution Of Abdominal Appendagesmentioning
confidence: 99%
See 1 more Smart Citation
“…The E complex was presumed to be analogous to the D. melanogaster bithorax complex (BX-C; Ueno et al, 1992) and studies on B. mori BX-C genes have suggested that all of them are involved in proleg patterning (Masumoto et al, 2009;Tomita and Kikuchi, 2009). However, the Hox genes are complex and few of these mutants have been characterized at the molecular level.…”
Section: Introductionmentioning
confidence: 99%